2007
DOI: 10.1093/eurheartj/ehm517
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption, TaqIB polymorphism of cholesteryl ester transfer protein, high-density lipoprotein cholesterol, and risk of coronary heart disease in men and women

Abstract: The association of alcohol with HDL-C levels was modified by CETP TaqIB2 carrier status, and there was also a suggestion of a gene-environment interaction on the risk of CHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 49 publications
4
61
0
Order By: Relevance
“…A classic example is the study of Fumeron et al ( 17 ) in French males in which a gene-alcohol interaction was described where the effect of B2 on HDL-C concentrations was absent in subjects drinking <25 g/d of alcohol but increased at higher levels. Following this observation, many studies have been published with inconsistent results ( 9,(18)(19)(20)(21)(22)38 ). In a prior study ( 20 ), we found no signifi cant TaqIBalcohol interaction in determining HDL-C in a healthy Mediterranean population.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…A classic example is the study of Fumeron et al ( 17 ) in French males in which a gene-alcohol interaction was described where the effect of B2 on HDL-C concentrations was absent in subjects drinking <25 g/d of alcohol but increased at higher levels. Following this observation, many studies have been published with inconsistent results ( 9,(18)(19)(20)(21)(22)38 ). In a prior study ( 20 ), we found no signifi cant TaqIBalcohol interaction in determining HDL-C in a healthy Mediterranean population.…”
Section: Discussionsupporting
confidence: 48%
“…Regarding prior studies that have analyzed gene-environmental interactions, a lack of consistency is observed. Some studies have reported that alcohol consumption statistically interacts with the TaqIB SNP and modifi es its effects on HDL-C concentrations (17)(18)(19), whereas others have not supported this interaction (20)(21)(22). Likewise, although there is one observational study ( 23 ) in which a statistically signifi cant interaction between the TaqIB-SNP and fat intake was found, those results have not been replicated ( 24 ).…”
Section: Demographic Clinical Anthropometric and Dietary Measurementsmentioning
confidence: 99%
“…Similarly, the newly identifi ed GWA genes, MVK and MMAB, have been recently shown to modulate plasma HDL-C levels depending on carbohydrate consumption ( 225 ), which may help elucidate their role in HDL metabolism. A geneenvironment interaction was also observed between the TaqIB polymorphism in CETP (rs708272) and alcohol consumption ( 226 ).…”
Section: Family Studies In Investigation Of Private Variantsmentioning
confidence: 83%
“…Two previous meta-analyses have documented that CETP genetic variants related to moderate inhibition of CETP activity were associated with favorable blood lipid levels and decreased cardiovascular risk ( 10,11 ). Several observational studies reported that CETP variants might interact with dietary factors, especially dietary fat intake, on HDL cholesterol levels (12)(13)(14)(15), although the fi ndings were not consistently replicated ( 11,(16)(17)(18)(19)(20). In addition, two small short-term diet intervention studies did not demonstrate the interaction between CETP genotype and dietary fat intake ( 21,22 ).…”
Section: Discussionmentioning
confidence: 99%